Characterization of tool wear in i-FSW of AISI 316L material joining. (2021) - Singh, Dilip K.; Sengupta, Kaushik; Mondal, Arpan K.; das choudhry, Ivy; Bose, D.; Singh, P.
Abstract: The i-FSW performed by using Nichrome coil pre-heating to the specimen dimension 100 × 75 × 2 mm of AISI 316L material to achieve the desire temperature and make successful friction stir welding. The experiment conducted on conventional milling machine by using TWC tool, whereas the pin length is 1.6 mm and pin diameter is 2.8 mm. The range of spindle rotation 600, 800 & 1000 revolution per min with welding speed of 15, 20 & 25 mm/min. The induction coil set inside the base plate and insulated with Fiber Glass Tape. The pre-heating temperature achieved 120°Celsius, which slightly increase the heat affected zone but also reduce the heat stresses inclusion. The additional heat source provide enough heat energy to produce fine grain size and achieve maximum strength of the weld joint. The experimentation has proved that the i-FSW welding of AISI 316L material is successful and pre-heating of specimen reduces the tool wear of 40% in comparison with normal FSW of specimen. The maximum mechanical properties such as UTS achieved 504 N/mm 2 with 97% welding efficiency.